Clima institucional y desempeño en docentes en la Institución Educativa N° Micaela Bastidas de Iquitos 2021 - Pacaya Flores, Marcos David (2022)
The objective of the research was: To determine that the institutional climate is related to the performance of the teachers of the Educational Institution No. 601050 "Micaela Bastidas" of Iquitos 2021. It was raised as a general problem: How does the Institutional Climate influence the Performance of the Teachers of the Educational Institution No. 601050 "Micaela Bastidas" of Iquitos 2021? And as specific objectives: Describe the institutional climate in the teachers of the Educational Institution No. 601050 "Micaela Bastidas" of Iquitos 2021. Evaluate the performance of the teachers of the Educational Institution No. 601050 "Micaela Bastidas" of Iquitos 2021. Establish the relationship between the institutional climate and performance in the teachers of the Educational Institution No. 601050 "Micaela Bastidas" of Iquitos 2021. The type of research used was descriptive correlational, whose general design was non-experimental and the specific design was cross-sectional correlational. The Population was 120 teachers. The sample size was made up of 91 teachers from the I.E Nº 601050 "Micaela Bastidas". Statistics were used for populations less than 1,500. The analysis of results was carried out using the non-parametric descriptive and inferential statistics Chi Square (X2) it was found: X2c = 15.9 > X2t = 9.48, gl = 4, p < 0.05%, concluding that: The institutional climate is related to a degree moderate with the performance of teachers. Therefore, it is recommended to the authorities of the Educational Institution No. 601050 "Micaela Bastidas" of the city of Iquitos, to permanently carry out actions to evaluate the performance of their teachers so that they improve their professional practice to provide students with a higher education.